Analyzing the push and pull travel motivation factor of youth tourist towards visiting Johor Bahru - Mohd Erfino, Syamim Syauqi; Md Sawari, Siti Salwa (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh, 2019)
Youth travellers are becoming an increasingly important market for tourism industry players. The trend of youth tourism is expected to rise up to 300 million travellers by 2020 and dominate one sixth of the global tourists’ market. The study has also identified that majority (70 percent) of young people travel for specific purpose. The purpose of this study is to identify the major push and pull factor that influence the youth tourist by analyzing decision making process. The study adopted a questionnaire survey that determine their source of motivation to travel and involved youth travellers (mainly students from universities and other institutes) within the age of 15 to 30 years. The data will be analyzed using SPSS software by employing descriptive analysis and standard multiple regression. The findings of this study indicate that there are multiple major factors for young people when choosing their motivation to travel to a city in Malaysia. Further analysis shows that there are significant differences among several motivation factors when it comes to local and international youth traveler. The contribution of this study is its indication towards which factors influence city destination choice among youth which will further enable Malaysian cities to develop and promote more appropriate and satisfactory tourism products and services for their young visitors.